Zanubrutinib in Treating Waldenström Macroglobulinemia, the Last Shall Be the First - Deshpande A; Munoz J (Dove Medical Press, 2022)
Anagha Deshpande,1 Javier Munoz2 1Mayo Clinic Alix School of Medicine, Scottsdale, AZ, USA; 2Division of Hematology and Oncology, Mayo Clinic, Phoenix, AZ, USACorrespondence: Anagha Deshpande, Mayo Clinic Alix School of Medicine, 13400 E Shea Blvd, Scottsdale, AZ, 85259, USA, Tel +1 480 251-0289, Email deshpande.anagha@mayo.eduAbstract: In Waldenström macroglobulinemia (WM), a lymphoplasmacytic lymphoma characterized by monoclonal immunoglobulin M (IgM) gammopathy, aberrant Bruton tyrosine kinase (BTK) signaling has been identified as one mechanism of pathogenesis. For this reason, selective BTK inhibiting therapies have emerged as an attractive option for treatment within the therapeutic landscape also comprising chemotherapy, monoclonal antibodies, proteasome inhibitors, and B-cell lymphoma 2 (BCL2) inhibitors. The first BTK inhibiting therapy, ibrutinib, showed great efficacy in treating WM. However, response rates were dependent on whether patients had the CXCR4 mutation, a molecular aberration that may confer resistance to BTK inhibitors. Furthermore, ibrutinib's toxicities, most notably hypertension and atrial arrhythmia, led to dose reductions or discontinuation. The toxicity profile of ibrutinib can be attributed to the inhibition of additional kinases that are structurally related to BTK. Therefore, the next-generation highly selective zanubrutinib was developed to address the concerns regarding toxicity and tolerance related to ibrutinib therapy. Based on the results of the randomized, open-label Phase 3 ASPEN (NCT03053440) trial, the Food and Drug Administration (FDA) approved zanubrutinib for treating WM. This trial directly compared zanubrutinib to ibrutinib in patients with treatment-naïve or relapsed/refractory WM, and the results showed stronger responses with zanubrutinib. More importantly, patients responded strongly to zanubrutinib therapy regardless of CXCR4 mutation status. Additionally, zanubrutinib was associated with fewer grade 3 or higher toxicities and was generally better tolerated. Another Phase 1/2 study has been conducted with just zanubrutinib in WM showcasing high efficacy with few toxicities as well. Even though zanubrutinib has been the third and last BTK inhibitor to currently penetrate the market for B-cell lymphoproliferative malignancies, we highlight the emergence of zanubrutinib as a key player in the forefront of the therapeutic landscape in WM.Keywords: zanubrutinib, Waldenström macroglobulinemia, Bruton tyrosine kinase inhibitor, ibrutinib, rituximab, efficacy, safety, atrial fibrillation